PENGARUH GAYA KEPEMIMPINAN KEPALA SEKOLAH DAN LINGKUNGAN KERJA TERHADAP KEPUASAN KERJA GURU SMK PANCA DHARMA BALIKPAPAN - jurnalpps pps; Taufan Taufan; Indra Prasetyo; c Sri Hartati (Jurnal Manajerial Bisnis, 2021)
This study aims to determine the effect of the principal's leadership style and work environment on job satisfaction of teachers at Panca Dharma Balikpapan Senior High School, East Kalimantan Province, either partially or simultaneously. The research method used is explanatory research with a total population of 32 teachers with a total sampling method. The data analysis method used is statistical analysis. The results showed; There is an influence of the principal's leadership style and the work environment either partially or collectively which has a significant effect on teacher job satisfaction, respondents' assessment of the principal's leadership style and work environment on teacher job satisfaction in both categories. And the better the leadership style of the principal and the work environment, the better the job satisfaction of teachers in the SMKS Panca Dharma Balikpapan.